Factors determining the extent of GDPR implementation within organizations: empirical evidence from Czech Republic - Faifr, Adam; Januška, Martin (Journal of Business Economics and Management, 2021)
In this paper, the key factors that affect the extent of GDPR implementation in enterprises are analysed. Since 2018, all organizations operating in the European Union or processing personal data of EU citizens have had to incorporate a new regulation in their work. After three years of experience, possible key factors that significantly affect the cost of the entire project have been theoretically identified. However, a research gap remains whether the factors thus defined actually have a real impact on the implementation within organizations. Therefore, this study focuses on an empirical investigation of those characteristics using quantitative approach combining Chi-squared tests and the Classification and Regression Tree method. Based on a survey of organizations in the Czech Republic, this paper outlines that the size of the organization, the typology of personal data processed and the way GDPR is implemented determine the scope of the implementation project within organizations. On the other hand, there is no clear evidence that there is significant role in whether it is a public or private organization.